2003
DOI: 10.1097/00024382-200301000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Association of a TNF?? Gene Polymorphism with Complications After Major Abdominal Operations

Abstract: In injured patients, it has been shown that a polymorphism of the tumor necrosis factor-beta (TNFbeta) gene is related to the development of sepsis. We investigated the relation of TNFbeta gene polymorphism with the development of severe complications after elective major abdominal operations, and with production of TNFalpha perioperatively. In the present investigation, the Ncol polymorphism was studied in genomic DNA isolated from the blood of 172 patients. Preoperatively and postoperatively, lipopolysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 11 publications
0
19
0
3
Order By: Relevance
“…Given the small number of -308A homozygotes, homozygotes for the -308A allele were grouped with the heterozygotes (-308A), and compared with -308G homozygotes in the final model, as in prior reports [15,16]. As the distribution of the TNFB genotype among cases and controls did not clearly suggest a dominant or recessive model, the TNFB genotype was modelled as in previous reports [17,18] by comparing TNFB2 homozygotes (TNFB22) with homozygotes and heterozygotes for TNFB1. C-statistics (area under the receiver operating characteristic curve) were used to evaluate model fit [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the small number of -308A homozygotes, homozygotes for the -308A allele were grouped with the heterozygotes (-308A), and compared with -308G homozygotes in the final model, as in prior reports [15,16]. As the distribution of the TNFB genotype among cases and controls did not clearly suggest a dominant or recessive model, the TNFB genotype was modelled as in previous reports [17,18] by comparing TNFB2 homozygotes (TNFB22) with homozygotes and heterozygotes for TNFB1. C-statistics (area under the receiver operating characteristic curve) were used to evaluate model fit [27].…”
Section: Discussionmentioning
confidence: 99%
“…Carriers of the -308A allele (-308A) and homozygotes for the TNFB2 allele (TNFB22) have increased TNF-a production [14,15] and increased susceptibility to, or increased mortality in, septic shock in some studies [15][16][17][18][19], but not in others [20,21].…”
mentioning
confidence: 99%
“…Although earlier concepts of the pathophysiology of sepsis regarded these cytokines mainly as mediators of shock and cell damage, newer findings have demonstrated that a certain level of production of these cytokines is necessary for a patient to survive sepsis. In this context, Riese et al found an association between complications and a postoperatively reduced capacity of macrophages to secrete cytokines (23 ).…”
Section: Discussionmentioning
confidence: 99%
“…At some point in the future, patients may receive preoperative genetic screening to predict their susceptibility to perioperative lactic acidosis and other surgical complications. 41 …”
Section: Comment By Barry a Mizock MD And Cory Franklin Mdmentioning
confidence: 99%